2002
DOI: 10.1097/00024382-200210000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-?? Production Is Suppressed in Thermally Injured Mice: Decreased Production of Regulatory Cytokines and Corresponding Receptors

Abstract: Thermal injury to 40% or more of the total body surface area poses a significant risk for the development of opportunistic infections that increase complications and mortality. Altered cytokine induction profiles, including suppression of the Th1 cytokines IFN-gamma and IL-12 and elevations in the anti-inflammatory cytokine IL-10, are believed to contribute to burn-associated immunosuppression and the development of sepsis. The specific changes that lead to altered cytokine production following major burns are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…The IL-18 response after bacterial infection might be closely related to IFN-␥ production and thereby to the host defense mechanism, particularly regarding cellular immunity against postburn bacterial infections. Toliver-Kinsky et al (51,52) studied the mechanism of immune suppression after burn injury and claimed that IFN-␥ production was suppressed after P. aeruginosa infection; but they used heatkilled P. aeruginosa, and we have also shown similar results using heat-killed P. aeruginosa. Horvat et al (27) and Parmely et al (28) have demonstrated that some P. aeruginosa strains secrete alkaline protease and elastase and thereby inactivate recombinant IFN-␥.…”
Section: Discussionsupporting
confidence: 63%
“…The IL-18 response after bacterial infection might be closely related to IFN-␥ production and thereby to the host defense mechanism, particularly regarding cellular immunity against postburn bacterial infections. Toliver-Kinsky et al (51,52) studied the mechanism of immune suppression after burn injury and claimed that IFN-␥ production was suppressed after P. aeruginosa infection; but they used heatkilled P. aeruginosa, and we have also shown similar results using heat-killed P. aeruginosa. Horvat et al (27) and Parmely et al (28) have demonstrated that some P. aeruginosa strains secrete alkaline protease and elastase and thereby inactivate recombinant IFN-␥.…”
Section: Discussionsupporting
confidence: 63%
“…IFN-g and IL-12 are normally elevated in response to systemic bacterial challenge. 27,28 The significance of low IFN-g and IL-12 concentrations in blood and peritoneal fluid following CLP is not completely clear but further brings into question the functional role of bacteremia in CLP-induced death. However, Echtenacher et al 29 showed that neutralization of IFN-g and IL-12 does not alter mortality in mice exposed to CLP.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is often termed immunoparalysis or postinflammatory immunosuppression and is characterized by decreased production of gamma interferon (IFN-␥) and interleukin-12 (IL-12) as well as increased secretion of the antiinflammatory cytokine IL-10 in response to an infectious challenge. Some researchers have proposed that the state of endotoxin (lipopolysaccharide [LPS]) tolerance is a model of immunoparalysis because LPS-tolerant animals exhibit a pattern of cytokine production that is nearly identical to that observed during postinflammatory immunosuppression (10,28,31). LPS tolerance is induced by exposure to sublethal doses of LPS, which results in a suppressed proinflammatory response and improved survival after challenge with a normally lethal dose of LPS (4,15).…”
mentioning
confidence: 99%
“…IFN-␥ production is induced by the macrophage-and dendritic cell-derived cytokines IL-12, IL-15, and IL-18, which are produced after engagement of pattern recognition receptors by bacterial products such as LPS. Suppressed secretion of these cytokines is reported to be a hallmark of injury-induced immunoparalysis (20,28). In contrast, elevated levels of IL-10 may suppress antimicrobial immunity and render the host more susceptible to infections (28).…”
mentioning
confidence: 99%